2006
DOI: 10.1002/cne.21190
|View full text |Cite
|
Sign up to set email alerts
|

Chemoarchitecture of the middle temporal visual area in the marmoset monkey (Callithrix jacchus): Laminar distribution of calcium‐binding proteins (calbindin, parvalbumin) and nonphosphorylated neurofilament

Abstract: We studied the distributions of interneurons containing the calcium-binding proteins parvalbumin and calbindin D-28k, as well as that of pyramidal neurons containing nonphosphorylated neurofilament (NNF), in the middle temporal visual area (MT) of marmoset monkeys. The distributions of these classes of cells in MT are distinct from those found in adjacent areas. Similar to the primary visual area (V1), in MT, calbindin-immunopositive neurons can be objectively classified into "dark" and "light" subtypes based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 92 publications
(131 reference statements)
5
30
2
1
Order By: Relevance
“…We compare our results with those described in Macaca as well as in squirrel monkey (Duffy and Livingstone, 2003) and marmoset (Bourne and Rosa, 2003;Bourne et al, 2007). Smaller New World monkeys like marmoset show a weaker degree of laminar organization in the LGN and a lack or weaker degree of eye input segregation in layer 4 in the primary visual cortex.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…We compare our results with those described in Macaca as well as in squirrel monkey (Duffy and Livingstone, 2003) and marmoset (Bourne and Rosa, 2003;Bourne et al, 2007). Smaller New World monkeys like marmoset show a weaker degree of laminar organization in the LGN and a lack or weaker degree of eye input segregation in layer 4 in the primary visual cortex.…”
supporting
confidence: 54%
“…In contrast, in smaller New World monkeys, fewer cortical fields are present in the corresponding parietal location. It has been suggested that there are differences in the chemoarchitectural pattern even between members of the same order and that these are important in tracing evolutionary adaptations and phylogenetic relationships (Bourne et al, 2007). Thus, the present study, on the distribution of neurofilament protein in the LGN and in areas V1 and MT in Cebus, will allow comparison of the cytochemical organization of these structures in New and Old World monkeys.…”
mentioning
confidence: 88%
“…The manatee mainly exhibited light staining in layers IIIc and parts of VI, and heavy staining in layer V, while cetaceans have heavy staining in the combined layer IIIc/V . This pattern differs from what is seen in primates, rodents and carnivores, where staining is more diffusely distributed throughout the cortex wherever there are pyramidal neurons [Campbell and Morrison, 1989;Chaudhuri et al, 1996;Hof et al, 1996;Nimchinsky et al, 1997;Preuss et al, 1997;Budinger et al, 2000;Tsang et al, 2000;Van der Gucht et al, 2001;Sherwood et al, 2004;Baldauf, 2005;Boire et al, 2005;Bourne et al, 2005;Hof and Sherwood, 2005;Bourne et al, 2007;Van der Gucht et al, 2007] but is similar to what is also observed in afrotherians, xenarthrans, monotremes and marsupials Hassiotis et al, 2005;Sherwood et al, 2009]. Primates, rodents and carnivores also have different patterns of NPNFP-ir neuron distribution in different cortical areas [Campbell and Morrison, 1989;Campbell et al, 1991;Hof and Nimchinsky, 1992;Budinger et al, 2000;Van der Gucht et al, 2001, which is not as clearly variable across the cortex in afrotherians, xenarthrans, monotremes and marsupials Ashwell et al, 2005;Hassiotis and Paxinos, 2004;Hassiotis et al, 2005;Sherwood et al, 2009].…”
Section: Possible Factors Influencing Manatee Neuron Types and Districontrasting
confidence: 55%
“…K1 and K2 project directly to the middle temporal area (MT) in the cortex (Bourne et al, 2007). Studies involving blindsight have suggested that projections from the LGN not only travel to V1, but also to the higher cortical areas including secondary (V2) and tertiary (V3) visual cortex (Schmid et al, 2010).…”
Section: Marmoset Gene Expression In the Dlgnmentioning
confidence: 99%